Loss of Guide Vane Disposition on Francis Turbine of Unit 6 of the Hydroelectric Power Plant PLTA - Ghozali, Syaiful; Alqap, A Sofwan F; Helmizar, Helmizar (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2021)
Hydropower is a power plant (PLTA) that is very environmentally friendly because it is clean and does not pollute the environment compared to other plants. PLTA, one of which is located in Bengkulu Province, is a power plant that utilizes the potential energy of water. Where the source of the water propulsion produced for the process of generating electricity is from the Tes lake which is sourced from the Air Ketahun river and the Air Pauh river, Lebong Bengkulu. Where this PLTA uses a Francis type turbine with a horizontal position. PLTA has 7 turbine units, with units 1 and 2 being old units producing 2 x 600 KW of power, while units 3 – 7 producing 5 x 4400 KW of power, so the total installed power is 23,200 KW. One of the problems that often occurs in PLTA is the occurrence of disposition of the guide vane on the turbine, where this time we will find out the cause of the disposition and how to overcome it so that there is no disposition and find out the loss of disposition of the guide vane on the Francis unit 6 turbine at PLTA. With this research done, the disposition occurs, it is necessary to take corrective action so that the unit will stop operating and can affect the level of profitability of the company. So that the results of the unit's work if it operates 24 hours are approximately 82 million rupiah, repairs are carried out for 16 hours with a loss of approximately 55 million rupiah. The occurrence of disposition is caused by damage to the transrack so that large waste enters the turbine section. In order to prevent disposition, it is necessary to repair or replace the transrack at the inlet.